The relationship between nursing students' quality of life with their academic achievement motivation in isfahan university of medical sciences, Iran - SeyedehMahtab Emamjomeh; Ali Toghyani; Masoud Bahrami (Wolters Kluwer Medknow Publications, 2021)
Background: Quality of Life (QoL) and academic achievement motivation are important aspects of students' living and studying. There is a lack of studies to address the QoL of nursing students and its relationship with their academic achievement motivation in Iran. Therefore, the present study was conducted to investigate this relationship. Materials and Methods: This was a correlational study conducted with baccalaureate nursing students of Isfahan University of Medical Sciences, Iran, from December 2019 to February 2020. Data collection tools consisted of three parts: a demographic questionnaire, the World Health Organization QoL-Brief Questionnaire (WHOQOL-BREF), and the Hermans Achievement Motivation Questionnaire. Pearson correlation coefficient and standard multiple regression were used to evaluate the correlation between QoL mean domain scores and academic achievement motivation score. Results: The QoL mean (SD) domain scores of physical, psychological, social, environmental, and academic achievement motivation score were 14.95 (2.43), 13.42 (2.74), 13.96 (3.39), 13.62 (2.54), and 84.40 (7.73), respectively. Pearson correlations between physical, psychological, social, and environmental QoL mean domain scores with academic achievement motivation score was 0.30, 0.35, 0.12, and 0.22 (p < 0.05), respectively. Using standard multiple regression, psychological mean domain score (ß = 0.31) was the only statistically significant predictor of academic achievement motivation. Conclusions: Relationships exist between academic achievement motivation and QoL domains of nursing students, particularly in the psychological domain. This information provides policymakers to plan multi-faceted arrangements to improve nursing students' academic achievement motivation and QoL particularly in most neglected areas as the psychological aspect.